Gabungan Kelompok Tani (Gapoktan) Tani Mulyo Sebagai Relawan Bantuan Hidup Dasar (BHD) dalam Mewujudkan Daerah Pertanian Ramah Jantung - Yunanto, Rismawan Adi; Wantiyah, Wantiyah; Rokhmah, Dewi; Setioputro, Baskoro; Haristiani, Ruris (Universitas Nusantara PGRI Kediri, 2023)
The incidence of heart attack is one of the highest causes of death in the world and Indonesia. East Java ranks second highest for people with heart problems who risk getting a heart attack. The farmers had a high-risk factor for heart disease due to an unhealthy lifestyle (high-fat diet, smoking, caffeine consumption, and exposure to pesticides). Farmers in Suci Village, Panti District, Jember Regency also have the same risk. Farmers in the Sacred Village had a high enough risk of a heart attack. This is the reason for the Mulyo Farmers Group Association (Gapoktan), Suci Village, Panti District, Jember Regency, to be empowered in dealing with this problem. The purpose of implementing this service is to create a heart-friendly agricultural area in Suci Village by downstream the research results of the proposer team, increasing knowledge, attitudes, and skills of Gapoktan about BHD, and forming a group of volunteers for BHD Gapoktan Tani Mulyo. The method used starts with initial identification with partners, formulation of activities, implementation of activities, and final dissemination. The result is that Tani Mulyo's Gapoktan has been empowered to become a BHD volunteer. The results of our program implementation were evaluated by giving pretest and post-test questionnaires, which we analyzed with a dependent t-test. The result showed that there was a significant increase in the variables of knowledge (p=<0.001), attitude (p=0.003), and skills (p=<0.001) from Tani Mulyo's Gapoktan. With the implementation of this service, Tani Mulyo Gapoktan has been empowered to become a BHD volunteer to create a heart-friendly agricultural area.